Jacalin regulates IgA production by peripheral blood mononuclear cells. (December 2012) - Miyamoto, Keiichi; Chiba, Takeshi; Shinohara, Noriko; Nagata, Yuko; Asakawa, Nagisa; Kato, Shinji; Mizutani, Naoki; Murata, Tomohiro; Nomura, Shinsuke; Horiuchi, Takashi
Aims: In IgA nephropathy, circulating immune complexes containing IgA1 are deposited on the glomerular mesangium, causing mesangial cell proliferation and acceleration of extracellular matrix production. The suppressive effect of jacalin, a galactose-binding lectin, on IgA production in vitro was determined.Materials & methods: Normal human peripheral blood mononuclear cells were stimulated with plate-bound anti-CD3 and Th2 stimulation, with or without jacalin. Regulatory and effector cell subsets were determined by flow cytometry, and immunoglobulin production by ELISA.Results: Jacalin increased the ratio of CD4 + CD25 + CD152 + Tregs:effector T cells in peripheral blood mononuclear cell cultures 60-fold. This CD4 + CD25 + CD152 + Treg increase may have inhibited Th2-stimulated IgA production by B cells.Conclusion: Immune tolerance induced by jacalin can suppress IgA production.